KONVERGENSI POLITIK ISLAM: PERILAKU ELEKTORAL WARGA NU TRENGGALEK TERHADAP PKS DAN DAMPAKNYA BAGI PETA POLITIK LOKAL - Agus Cahyono; Teguh Teguh; Akhmad Rizqon Khamami (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
This study aims to examine the phenomenon of Islamic political convergence through the electoral behavior of Nahdlatul Ulama (NU) members in Trenggalek towards the Prosperous Justice Party (PKS) and to analyze its impact on the configuration and dynamics of the local political map. This phenomenon is interesting because historically, NU is known to have cultural and political closeness to the National Awakening Party (PKB), while PKS is more representative of the modernist Islamic movement. Changes in the orientation of NU voters who show affiliation or sympathy towards PKS raise theoretical and empirical questions regarding the shift in Islamic political identity and the potential for the formation of new political spaces at the local level. The method used in this study isSystematic Literature Review(SLR) on 21 scientific articles published in the period 2013-2023, both from accredited national journals and reputable international journals. The articles reviewed were evaluated based on the suitability of the focus on the theme of Islamic political convergence, the relationship between NU and PKS, and changes in voter behavior at the local level. The results of the analysis show that political convergence between NU and PKS members is made possible by political pragmatism factors, PKS's inclusive digital preaching strategy, and the weakening of the ideological identity of traditional mass-based parties. In Trenggalek, this tendency has an impact on the shifting configuration of local political power, the weakening of PKB's dominance, and the emergence of a new electoral coalition configuration. In conclusion, Islamic political convergence opens up opportunities for more competitive local democratic dynamics, but at the same time challenges traditional ideological identities. The implications are important to consider in campaign design, Islamic political consolidation, and strengthening the value-based voter base.